Bosnia and Herzegovina 2001-2004 : Enterprise Restructuring, Labor Market Transitions and Poverty - Tiongson, Erwin R. (World Bank, Washington, DC, 2012)
This paper takes stock of labor market developments in Bosnia and Herzegovina over the period 2001-2004, using the panel Living Standards Measurement Study/Living in Bosnia and Herzegovina survey. The analysis estimates a multinomial logit model of labor market transitions by state of origin (employment, unemployment, and inactivity) following the specification of widely used models of transition probabilities, and analyzes the impact of standard covariates. The results provide strong evidence that there are indeed significant differences in labor market transitions by gender, age, education, and geographic location. Using the panel structure of the multi-topic survey data, the authors find that these transitions are related to welfare dynamics, with welfare levels evolving differently for various groups depending on their labor market trajectories. The findings show that current labor market trends reflecting women's movement out of labor markets and laid-off male workers accepting informal sector jobs characterized by low productivity will lead to adverse social outcomes. These outcomes could be averted if the planned enterprise reform program creates a more favorable business environment and leads to faster restructuring and growth of firms.